Physiological genetics of the response to a high-sucrose diet by Drosophila melanogaster. - Wang, L.; Clark, A.G. (Biochemical Genetics, 1995)
A diet medium containing 10% (w/v) sucrose can be inferred to be stressful to Drosophila melanogaster from the increased developmental time and reduced size and fecundity of emerging flies. The metabolic basis for this stress and the genetic response to it are of interest from the point of view of both metabolic regulation and the evolutionary genetics of adaptation to stress. Here the effects of a high-sucrose diet on live weight, total protein, stored lipid and glycogen, and crude activities of 12 enzymes involved in energy metabolism were quantified. Assays were done on a large population of Drosophila that had been acclimated to the laboratory. A collection of eggs was divided to produce two replicate populations maintained on standard medium and two replicates maintained on high-sucrose medium for 133 generations. At the end of this period, both control and sucrose-selected populations were tested on standard and on high-sucrose medium. Results showed that the immediate effect of the high-sucrose diet (compared to standard medium) for both populations was a reduction in live weight and total protein, and activities of many of the enzymes were also reduced by the sucrose treatment, even after adjusting for the weight effect. Selection resulted in several changes on both the standard and the sucrose medium, but the direction of change was not always the same as the acute effect. In no case was there a significant medium by selection-treatment interaction. The pattern of phenotypic correlations did not resolve the reasons for the direction of the genetic responses. Correlations were generally stable across diets and after selection, but there were notable exceptions.